Potential prevalence, pattern, and risk factors of insomnia symptoms in adolescent elite athletes - Gerber, M.; Kellmann, M.; Lang, C.; Brand, S.; Gygax, B.; Ludyga, S.; Müller, C.; Ramseyer, S.; Jakowski, S. (Zeitschrift für Sportpsychologie, 2022)
Sleep disorders are an important issue among elite athletes. In this study, we used data from two studies to examine the prevalence, pattern, and risk factors of insomnia symptoms among adolescent elite athletes. We assessed insomnia symptoms using the Insomnia Severity Index. The prevalence of moderate-to-severe insomnia varied between 5 - 11 %, with 36 - 54 % of the athletes reporting subthreshold insomnia and 61 - 73 % perceiving at least one insomnia symptom. Female participants were more prone to report insomnia symptoms. Dysfunctional sleep-related cognitions were the most critical risk factor. We identified three groups with distinct insomnia symptom patterns via latent class analyses: 43 % of the participants were characterized as healthy sleepers, 45 % reported medium sleep without heightened concerned about sleep problems, and 12 % reported poor sleep and were substantially worried/distressed about their impaired sleep. More information is needed on how dysfunctional sleep-related cognitions can be influenced to improve athletes` sleep and to foster their well-being. Schlafstörungen stellen bei Leistungssportler_innen ein wichtiges Problem dar. Im Rahmen von zwei Studien werden bei jugendlichen Leistungssportler_innen Prävalenz, Muster und Risikofaktoren von Schlaflosigkeitssymptomen untersucht. Symptome wurden mit dem Insomnia Severity Index erfasst. Die Prävalenz von mittelschwerer bis schwerer Schlaflosigkeit variierte zwischen 5 - 11 %, 36 - 54 % der Athlet_innen fielen in die Kategorie unterschwellige Schlaflosigkeit und 61 - 73 % nahmen mindestens ein Schlaflosigkeitssymptom wahr. Weibliche Studienteilnehmer_innen waren anfälliger für Schlaflosigkeitssymptome. Dysfunktionale schlafbezogene Kognitionen stellten den wichtigsten Risikofaktor dar. Über latente Klassenanalysen wurden drei Gruppen mit unterschiedlichen Symptomen von Schlaflosigkeit identifiziert: 43 % der Teilnehmer_innen wurden als gesunde Schläfer_innen charakterisiert, 45 % berichteten mittelmässig ausgeprägte Schlaflosigkeitssymptome, ohne sich allzu große Sorgen über ihren Schlaf zu machen, und 12 % berichteten von schlechtem Schlaf und waren erheblich beunruhigt über ihren gestörten Schlaf. Es werden mehr Informationen benötigt, wie dysfunktionale schlafbezogene Kognitionen beeinflusst werden können, um den Schlaf von jugendlichen Leistungssportler_innen zu verbessern und ihr Wohlbefinden zu fördern.